Effect of Using the Kinemaster Application on the Learning Outcomes of Natural Sciences of Students UPT SMPN 3 Pitu Riase - Lestari, Eka; M, Usman; Takdir, Muhammad; Hermansyah, Sam; Zain , Suardi (International Journal of Educational Narratives, 2023)
Background. This research was conducted at UPT SMP Negeri 3 Pitu Riase, precisely in Desa Compong, Kec. Pit Riase, Sidengreng Rappang Regency. Purpose. There are 2 variables in this study, namely the independent variable that affects the use of the Kinemaster application (x) and the dependent variable, namely the learning outcomes of Natural Science class VII UPT SMP Negeri 3 Pitu Riase students (y). Method. This study uses quantitative methods with the type of experimental research that aims to examine the effect of using the Kinemaster application on the learning outcomes of Natural Science students in class VII UPT SMP Negeri 3 Pitu Riase. Results. The results of this study concluded that the effect of using the Kinemaster application on social studies learning outcomes of students in class VII UPT SMP Negeri 3 Pitu Riase, this shows that the working hypothesis which states that there is an effect of using the Kinemaster application on social studies learning outcomes of students in class VII UPT SMP Negeri 3 Pitu Riase, is accepted. Conclusion. The collected test data were analyzed using the average formula. Based on the results of data analysis obtained X value = 83.4 > Y value = 69.64 so that it can be seen that there is an effect of using the Kinemaster application on the learning outcomes of students in class VII UPT SMP Negeri 3 Pit Riase.